Modeling the Permittivity of Ferrite-Dielectric Composites - V.A. Astakhov; R.I. Shakirzyanov; A.T. Morchenko; Z.V. Mingazheva; S.P. Kurochka (Журнал нано- та електронної фізики)
The paper presents the model of ferrite-dielectric (ferroelectric) composites with semiconductive powder fillers. Such media have the potential for designing systems with controlled frequency dispersion. Experimentally observed significant increase of effective dielectric permittivity in Mn-Zn ferrite composites with the semiconductor pellet is explained on the basis of the capacitance effect. Composites based on Ni-Zn ferrite, which have significantly higher electrical resistance, do not exhibit such phenomena and their behavior is described in the framework of the traditional models of effective medium approximation. There is proposed an analytical solution for the dielectric constant of the composite, based on consideration of the impedances of equivalent circuit involving initial materials (matrix and filler).